A critical review on the techniques used for the synthesis and applications of crystalline cellulose derived from agricultural wastes and forest residues. (1st December 2021) - Debnath, Banhisikha; Haldar, Dibyajyoti; Purkait, Mihir Kumar
Abstract: In order to meet the growing energy crisis of the 21st century, the utilization of bio-based materials has become a field of high research endeavour. In view of that, the present review paper is focused on different techniques that are frequently explored for the synthesis of value-added crystalline derivatives of cellulose like MCC and NCC from agricultural wastes and forest residues. Moreover, a comparative analysis between thermochemical and biochemical methods is carried out for such valorization of biomass considering the mechanism involved with various reactions. Further, a critical analysis is performed on various individual techniques specifically used for the applications of MCC and NCC in different fields including environmental, polymer industry, pharmaceutical and other emerging sectors. This article will assist the readers not only to explore new biomass sources but also provides an in-depth insight on various green and cost-effective methods for sustainable production of crystalline cellulose. Highlights: Potential of agricultural wastes and forest residues towards the production of crystalline cellulose was explored. The conventional methods of synthesis of MCC and NCC and the involved mechanisms were summarized. Comparison of the conventional thermochemical and biochemical methods was discussed. The various methods used for the environmental, industrial and other potential applications of MCC and NCC are summarized. Commercial aspects of MCC and NCC production from agricultural wastes and forest residues were discussed.